The Impact of Customer’s Perception of the Practices of Corporate Social Responsibility on Purchase Intention - Ahmed Sayed Rashed; Doaa Mohamed Abd Elsamea (STIE Malangkucecwara, 2021)
The scarcity of research on the customer`s perception towards corporate social responsibility (CSR) in developing countries has inspired this research. This study aims to measure the impact of the customer`s perception of the practice of corporate social responsibility on the purchase intention in the presence of the service quality as a mediator variable. To achieve the aims of this study, the researcher relied on the mixed design of the search. The relevant CSR literature was recapitulated into a conceptual framework and an empirical study that were conducted through a mixed research design. This study reached many of the results, including that there is a direct impact of corporate social responsibility on the purchase intention. Also, there is an indirect impact of the moderating variable of the study, which is service quality of the direct positive impact of both the economic dimension, Ethics and philanthropic on purchase intention.